Development and field evaluation of a low-cost automated drip irrigation system - SHARMA, NAVNEET; V.M., ABDUL HAKKIM; SINGH, ATUL KUMAR (Journal of Soil and Water Conservation, 2021)
The present study was conducted to design, develop and evaluate a low-cost automated drip irrigation system working on the basis of soil moisture content. In order to get popularity and wider adoption of automated drip irrigation system, it is essential to bring out a cost-effective system. The study involved fabrication of a soil moisture deficit-based drip automation system and testing of the system under field conditions. The system was tested and calibrated based on automatic irrigation scheduling. The automation system developed was simple, precise, sensitive, light weight, cost effective in construction and fast responding. The speed of measurement, cheapness and portability are the key advantages and the system is easily adaptable for use with automatic logging equipment. The automated system based on soil sensors was found to be working efficiently without frequent supervision and maintained the pre-set moisture content in the root zone. The low-cost automated drip irrigation system developed ensures better returns to Indian farmers through considerable savings in labour and other farm inputs. There is scope for further studies on optimization of the electrode geometry and evaluation of electrical conductivity-based soil moisture sensors with different fertilizer and chemical application.